STRATEGI PENGEMBANGAN PARIWISATA DI KABUPATEN PURWOREJO - Rika Mandhega Vimastalia; Diah Hariani; Hesti Lestari (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Purworejo tourism sector is supported by the availability of natural and other potential. Purworejo government has set a Regional Regulation No. 4 of 2009 where there are six tourist attractions that are a priority for development, among others: Jatimalang Beach, Seplawan Cave, Gegermenjangan Hill Resort, The Sign of WR. Soepratman, Keburuhan Beach, and Museum Tosan Aji. The problem faced are the condition of tourism that are not experiencing significant development, what factors inhibiting and supporting the development of tourism and how the strategy of tourism development in Purworejo. This research uses theories of strategic management, and SWOT analysis to identifying strengths, weaknesses, opportunities, threats, and strategic issues. The type of this research is qualitative descriptive. In conclusion, there are eight strategic issues of Purworejo tourism development. By using Litmus Test to evaluate these issues, there are six development strategies. The most strategic issue is cooperation with various business sectors.